Seeds, Markets, and Information - Smale, Melinda; King, Amanda (International Food Policy Research Institute, 2005)
Institutional analysis can be used to understand the value placed on crop diversity by farmers as a social process, and to uncover the market-related constraints and incentives that influence farmer management of genetic resources. This is particularly important for capturing the dynamics of crop populations and the collective impact of individual decisions regarding crop diversity.